Stimuli-responsive microcarriers and their application in tissue repair: A review of magnetic and electroactive microcarrier - LiYang Zhang; Mengjiao Ma; Junfei Li; Kun Qiao; Yajie Xie; Yudong Zheng (Bioactive Materials, 2024)
Microcarrier applications have made great advances in tissue engineering in recent years, which can load cells, drugs, and bioactive factors. These microcarriers can be minimally injected into the defect to help reconstruct a good microenvironment for tissue repair. In order to achieve more ideal performance and face more complex tissue damage, an increasing amount of effort has been focused on microcarriers that can actively respond to external stimuli. These microcarriers have the functions of directional movement, targeted enrichment, material release control, and providing signals conducive to tissue repair. Given the high controllability and designability of magnetic and electroactive microcarriers, the research progress of these microcarriers is highlighted in this review. Their structure, function and applications, potential tissue repair mechanisms, and challenges are discussed. In summary, through the design with clinical translation ability, meaningful and comprehensive experimental characterization, and in-depth study and application of tissue repair mechanisms, stimuli-responsive microcarriers have great potential in tissue repair.